PRAWA REPRODUKCYJNE I SEKSUALNE W ONZ I ICH DOKTRYNALNE UWARUNKOWANIA - Dobrowolska, Karolina (Zeszyty Prawnicze, 2016)
Sexual and Reproductive Health and Rights at the United Nations and Their Doctrinal Background Summary The concept of sexual and reproductive health and rights still remains unclear in the international law regime. Despite the fact that during the United Nations International Conference on Population and Development in Cairo (1994), all UN Member States agreed that the term sexual and reproductive health and rights does not contain the “right to abortion,” one can observe continuous attempts to renegotiate the established consensus. The discussion on SRHR is exerting a great impact on the policy of international organizations and therefore it has a potential to create obligations on their Member States. The aim of this article is to present the history of the concept of “sexual and reproductive health and rights” and to analyze it in two aspects. First, the article elaborates on the doctrinal and ideological connotations of SRHR construction. It shows how the SRHR construction derives from feminist theories that regard the spheres of procreation and sexuality as the main sources of inequality between men and women. Second, the article shows how feminist concepts of human sexuality have influenced and shaped the legal constructions of international treaties under the UN auspices.